RANCANG BANGUN ALAT PEMERAH SUSU ELEKTRIK - Pambudi, Sandhi Yuda; Widyantara, Helmy; Wibowo, Madha Christian (Journal of Control and Network Systems (JCONES), 2016)
In a rapid technological developments in the field of milking. Some various tools have been developed, especially in the field of milking. Milking tool now can be controlled automatically, and adjusted with people needs to a purpose making more easier when its Milking, but how ever the milk has to be hygenic, not polluted and guaranteed quality. To produce milk of assured quality, the handling, equipment, and milking should be done properly. If not handled properly, then the quality of the milk produced would not be in accordance with ISO standards predetermined number 01-3141-1998. The purpose of this thesis facilitate human in performing automatic milking. The working principle of this tool is similar to the principle milking manually, which namely by hand. With the ATmega 8 which works as the brain of the system, that runs all the input and output then perform milking according to what the author wants. This tool helps the farmers in performing milking the dairy animals in flexible and automated. With this too, it does not require manpower, just enough give a 12 volt DC power supply and the tool will work with the milking process stages milking as, delay 1s, 2s, 3s, 4s, and also determine the milk yield of each.